Accounting for Socio-Economic Context in Quantifying the Attractive and Repellent Influence of Built Environment on Firearms Violence in Multiple Cities - Muggy, Luke (Journal of quantitative criminology, 2024)
Objectives The objective of this paper is to improve understanding of the spatial relationship of the built environment (BE) with urban gun crime and how the influence of environmental features varies across geographic location and socioeconomic context. Specifically, we analyze associations between incidents of reported firearms violence and distance to built environment features, accounting for neighborhood socio-economic status. Methods This study compares reported crime data with the outputs from a Monte Carlo Simulation using the Network Cross-K Function for Stochastic Spatial Events on street networks. Where data is available, we examine ten features—transit stations, universities/colleges, convenience stores, gas stations, liquor licenses, alcohol outlets, tobacco retailers, lodging, restaurants, and schools—across diverse metropolitan areas to uncover features that exert “attractive” or “repellent” influence on firearms violence. We present results from four U.S. cities and examine how results vary by socio-economic status of census tracts. Results Attractive features include tobacco retailers in Pittsburgh, hotels/motels, alcohol outlets, and restaurants in New Orleans, and rail transit stations in Los Angeles. We uncover localized attractive and repellent relationships within the lowest and highest socio-economic areas. We also identify several firearms crime repellents, including universities/colleges and public/private schools. Conclusions We find that attractors vary by city and socio-economic status, indicating that the unique underlying environmental context of each city facilitates firearms crime differently.